Nieśmiałość a kompetencje temporalne młodzieży - Tucholska, Kinga; Tucholska, Stanisława (Acta Universitatis Lodziensis. Folia Psychologica, 2011)
The study refers to a problem of temporal competence in shy youth. The research question was: Whether and what differences in the level and the structure of temporal competences are in the group of young people with various level of shyness? The group of 286 (F–178, M–108) aged 15–18 years was tested. The Shyness Questionnaire by W. R. Crozier and The Temporal Competences Questionnaire by Z. Uchnast and K. Tucholska were applied. The analysis of results obtained allows to state that the shy youth has significantly lower level of temporal competence in general. They suffer from the lack of acceptance of their past and present situation, and deficit in prospective approach. The results of conducted research may direct the therapeutic work with shy people on the issues of their openness to various dimensions of psychological time. It should be noticed that the essence of shyness is not only in the lack of social or communicative competences but also it is connected with the lack of basic competences in psychological time experience.